Children’s Culture or Culture for Children? Some Philosophical Remarks on Early Years Art - Wendland, Michał (Sensus Historiae, 2023)
This study aims to introduce some philosophical commentaries and suggestions concerning early years theater (or early years art in general). Early childhood is a significant and distinct time in life that must be valued and supported in its own right. The concept of children’s participation in artistic practices still seems, however, not to be fully recognised and accepted. Leading fields of research struggle with the most basic definitions, e.g. the meanings of the term “childism” appear to contradict in different papers. Furthermore, the idea of children’s agency seems to transform these inaccuracies only partially and needs further development in order to avoid persistent misconceptions about childhood and early years art.